Israel's regime untangled between democracy and apartheid - Ariely, Gal (Cambridge University Press, 2021)
Israel attracts enormous attention among scholars, journalists, politicians, and the general public. Some regard the country as an apartheid regime that can only be challenged through boycotts and sanctions. Others believe it is a stable liberal democracy, created under extreme conditions. This book seeks to unravel these conflicting interpretations by focusing on three questions: How can the Israeli regime be classified? What are the borders of the Israeli regime? And what are the key factors that shape the regime and support its relative stability? Gal Ariely calls for an approach which disaggregates democracy into specific dimensions, examining the diverse aspects of the Israeli regime to determine the level of 'democraticness' exhibited rather than classifying the regime as a whole. In doing so he provides a comprehensive account of the Israeli regime, untangling conflicting interpretations and illustrates the advantages of using this approach for analysing disputed regimes more widely